Gelatin-assisted synthesis of ZnS hollow nanospheres: the microstructure tuning, formation mechanism and application for Pt-free photocatalytic hydrogen production. Issue 3 (15th December 2016) - Yan, Qing; Wu, Aiping; Yan, Haijing; Dong, Yuying; Tian, Chungui; Jiang, Baojiang; Fu, Honggang
Abstract : ZnS hollow nanospheres with tunable microstructures have been prepared through the gelatin-assisted hydrothermal process, which can be used as catalysts for Pt-free photocatalytic hydrogen evolution with good performance. Abstract : Nano-sized hollow spheres with tunable microstructures are urgently needed for their applications in advanced fields. The ZnS hollow spheres reported previously have usually required a complex multi-step process, and/or large size and/or less tunability in the microstructure. Here, a simple gelatin-assisted hydrothermal reaction of Zn(OAc)2 and thiourea was developed for the synthesis of ZnS hollow nanospheres. The size of the hollow spheres could be controlled below 100 nm with good homogeneity. The presence of gelatin is essential to decrease the size of ZnS particles and to form hollow structures. Only solid spheres with a large size were prepared in the absence of gelatin. The structure of hollow nanospheres could be regulated by altering the reaction parameters. Typically, the size of voids increases with prolonged reaction time. Also, the grain size of the hollow spheres increased with increasing reaction temperature (from about 3 nm to 10 nm) accompanied by a decrease in shell thickness. The results indicated that the hollow structure was formed through an "Ostwald ripening" process. The ZnS hollow nanospheres were used as catalyst for photocatalytic hydrogen production without additional co-catalyst. The maximum H2 production rate reached was 340 μmol h −1 (about 6.8 mmol h g).